arctan(x) + arctan(y) = arctan(\(\frac{x + y}{1 - xy}\))

We will learn how to prove the property of the inverse trigonometric function arctan(x) + arctan(y) = arctan(\(\frac{x + y}{1 - xy}\)), (i.e., tan\(^{-1}\) x + tan\(^{-1}\) y = tan\(^{-1}\) (\(\frac{x + y}{1 - xy}\)) if x > 0, y > 0 and xy < 1.

1. Prove that arctan(x) + arctan(y) = arctan(\(\frac{x + y}{1 - xy}\)), if x > 0, y > 0 and xy < 1.

Proof:

Let, tan\(^{-1}\) x = α and tan\(^{-1}\) y = β

From tan\(^{-1}\) x = α we get,

x = tan α

and from tan\(^{-1}\) y = β we get,

y = tan β

Now, tan (α + β) = (\(\frac{tan α + tan β}{1 - tan α tan β}\))

tan (α + β) = \(\frac{x + y}{1 - xy}\)

⇒ α + β = tan\(^{-1}\) (\(\frac{x + y}{1 - xy}\))

⇒ tan\(^{-1}\) x + tan\(^{-1}\) y = tan\(^{-1}\) (\(\frac{x + y}{1 - xy}\))

Therefore, tan\(^{-1}\) x + tan\(^{-1}\) y = tan\(^{-1}\) (\(\frac{x + y}{1 - xy}\)), if x > 0, y > 0 and xy < 1.


2. Prove that arctan(x) + arctan(y) = π + arctan(\(\frac{x + y}{1 - xy}\)), if x > 0, y > 0 and xy > 1. And

arctan(x) + arctan(y) =  arctan(\(\frac{x + y}{1 - xy}\)) - π, if x < 0, y < 0 and xy > 1.

Proof: If x > 0, y > 0 such that xy > 1, then \(\frac{x + y}{1 - xy}\) is positive and therefore, \(\frac{x + y}{1 - xy}\) is positive angle between 0° and 90°.

Similarly, if x < 0, y < 0 such that xy > 1, then \(\frac{x + y}{1 - xy}\) is positive and therefore, tan\(^{-1}\) (\(\frac{x + y}{1 - xy}\)) is a negative angle while tan\(^{-1}\) x + tan\(^{-1}\) y is a positive angle while tan\(^{-1}\) x + tan\(^{-1}\) y is a non-negative angle. Therefore, tan\(^{-1}\)  x + tan\(^{-1}\) y = π + tan\(^{-1}\) (\(\frac{x + y}{1 - xy}\)), if x > 0, y > 0 and xy > 1 and

arctan(x) + arctan(y) =  arctan(\(\frac{x + y}{1 - xy}\)) - π, if x < 0, y < 0 and xy > 1.


Solved examples on property of inverse circular function tan\(^{-1}\) x + tan\(^{-1}\) y = tan\(^{-1}\) (\(\frac{x + y}{1 - xy}\))

1. Prove that 4 (2 tan\(^{-1}\) \(\frac{1}{3}\) + tan\(^{-1}\) \(\frac{1}{7}\)) = π

Solution:  

2 tan\(^{-1}\) \(\frac{1}{3}\)

= tan\(^{-1}\) \(\frac{1}{3}\) + tan\(^{-1}\) \(\frac{1}{3}\)

= tan\(^{-1}\) (\(\frac{\frac{1}{3} + \frac{1}{3}}{1 - \frac{1}{3} • \frac{1}{3}}\))

= tan\(^{-1}\) \(\frac{3}{4}\)

Now L. H. S. = 4 (2 tan\(^{-1}\) \(\frac{1}{3}\) + tan\(^{-1}\) \(\frac{1}{7}\))

= 4 (tan\(^{-1}\) \(\frac{3}{4}\) + tan\(^{-1}\) \(\frac{1}{7}\))

= 4 tan\(^{-1}\) (\(\frac{\frac{3}{4} + \frac{1}{7}}{1 - \frac{3}{4} • \frac{1}{7}}\))

= 4 tan\(^{-1}\) (\(\frac{25}{28}\) x \(\frac{28}{25}\))

= 4 tan\(^{-1}\) 1

= 4 · \(\frac{π}{4}\)

= π = R.H.S.                        Proved.


2. Prove that, tan\(^{-1}\) \(\frac{1}{4}\) + tan\(^{-1}\) \(\frac{2}{9}\) + tan\(^{-1}\) \(\frac{1}{5}\) + tan\(^{-1}\) \(\frac{1}{8}\) = π/4.

Solution:

L. H. S. = tan\(^{-1}\) \(\frac{1}{4}\) + tan\(^{-1}\) \(\frac{2}{9}\) + tan\(^{-1}\) \(\frac{1}{5}\) + tan\(^{-1}\) \(\frac{1}{8}\)

= tan\(^{-1}\) \(\frac{\frac{1}{4} + \frac{2}{9}}{1 - \frac{1}{4} • \frac{2}{9}}\) + tan\(^{-1}\) \(\frac{\frac{1}{5} + \frac{1}{8}}{1 - \frac{1}{5} • \frac{1}{8}}\)

= tan\(^{-1}\) (\(\frac{17}{36}\) x \(\frac{36}{34}\)) + tan\(^{-1}\) (\(\frac{13}{40}\) x \(\frac{40}{39}\))

= tan\(^{-1}\) \(\frac{1}{2}\) + tan\(^{-1}\) \(\frac{1}{3}\)

= tan\(^{-1}\) \(\frac{\frac{1}{2} + \frac{1}{3}}{1 - \frac{1}{2} • \frac{1}{3}}\)

= tan\(^{-1}\) 1

=  \(\frac{π}{4}\) = R. H. S.                    Proved.


11 and 12 Grade Math

From arctan x + arctan y to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.